Religião e compromisso social: um estudo a partir do movimento de Jesus - Vieira, Ednaldo Rodrigues (2007)
This research project aims to study the relation between social commitment, departing from Jesus movement. Through historical and sociological bibliography, one seeks identifying the great problems of the society which Jesus lived in, (first-century Palestine under Roman empire s domination). Departing from the actual biblical bibliography, one makes a incursion in Mark s text in order to identify Jesus actuation, motivated by the compassion that he Jesus − demonstrated to excluded regarding to excluded crowds. This research shows up that Jesus, in his words and, over all, presents clear orientations to his discipleship so that they − his disciples themselves − also sympathize with the excluded crowds cause each one person, in particular this research also reveals that Jesus actuation and his movement´s that one beyond discipleship so that they-his disciples-themselves should also sympathize with the excluded crowds cause and each one´s in particular this research also reveals that Jesus actuation and his movement´s, beyond denouncing the profound social injustice which the excluded, marginalized crowd, were subdued to suggest a compromised practice with effective changes in social rapports, motivated by religious principles